Patient satisfaction with antiretroviral therapy services and associated factors at Gondar town health centers, Northwest Ethiopia: an institution-based cross-sectional study - Getaneh Adissu; Gashaw Andarge Biks; Koku Sisay Tamirat (BMC, 2020)
Abstract Background The Human Immunodeficiency Virus (HIV) with which over 37 million peoples are living is the leading cause of morbidity and mortality worldwide. The rapid expansion of antiretroviral treatment has dramatically reduced HIV related deaths and transmissions. Patient satisfaction could be an indispensable parameter used to measure patients' desired fulfillment by the services. Hence, this study aimed to determine the level of patient satisfaction with antiretroviral therapy services and determinants at Gondar town health centers. Methods An institution-based cross-sectional study was conducted from November 1 to 30, 2018. The systematic random sampling technique was used to select 663 HIV/AIDS patients on antiretroviral therapy follow-ups. Data were collected using a pretested interviewer-administered questionnaire and patient medical document reviews. Summary statistics such as means, medians and proportions were calculated and presented in the form of tables, graphs, and texts. Bivariate and multivariable logistic regression analysis was fitted and adjusted odds ratio (AOR) with a 95% confidence interval (CI) was computed to assess the strength of association. Variables with p-value 0.05 at multivariable logistic regression considered significant determinants of patient satisfaction. Results The overall patient satisfaction with antiretroviral therapy services was 75.4% (95%CI, 71.9 to 79%). Patients' age 38-47 years (AOR = 5.90, 95%CI: 3.38,10.31) and ≥ 48 years (AOR = 2.66, 95%CI:1.38,5.12), absence of signs and directions to ART clinic (AOR = 0.53,95%CI:0.35,0.82), Azezo health center (AOR = 2.68,95%CI:1.47,4.66) and Teda health center (AOR = 4.44,95%CI:1.73,11.30), and travel that took more than 1 h (AOR = 0.56;95% CI:0.32,0.97) were determinants of patient satisfaction with the services. Conclusion The overall patient satisfaction with antiretroviral therapy service was lower than the national target of 85% with the marked difference among health centers. Older age, absence of signs and directions to ART clinics, and longer travel from home to health centers were factors influencing patient satisfaction with antiretroviral treatments. This suggests that further improvement of accessibility is likely needed to increase patient satisfaction.